Perbandingan Hasil Belajar Siswa yang Diajar Dengan Menggunakan Model Contextual Teaching And Learning dan Guided Inquiry pada Pokok Bahasan Struktur Atom - Gulmah Sugiharti; Agus Muliaman (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. This study aims to determine whether there are differences in learning outcome is taught by models Contextual Teaching and Learning (CTL) and the model of Guided Inquiry (GI) and to investigate the cognitive level most growth in both classes. Sampling was done by purposive sampling technique by taking two classes of class X MIPA-1 and as the experimental class 1 and class X MIPA 9 as an experimental class 2. The instrument used to determine student learning outcomes is an objective test in the form of multiple choice questions numbered 30 which has proven validity, level of difficulty, power differentiator, distractors, and reliability. R_11 price obtained for the price rtabel = 0.892 and 0.312. overall reliability of the test can be said to be reliable because rhitung> rtabel. Class 1 is given treatment experiments using models Contextual Teaching and Learning and the experimental class 2 given treatment using a model of Guided Inquiry. After the pretest and posttest and data processing of the obtained χ2 Calculate pre-test 0.380 and χ2 Calculate post-test 0.319 for the experimental class 1 and χ2 Calculate pre-test 0.223 and χ2 Calculate post-test 0.107 for the experimental class 2 and value sign α = 0.05. Because χ2 Calculate> sign, then the normal distribution of data. At Fhitung homogeneity test showed a smaller number than the F table, namely 0.248> 0,05untuk value pretest, 0.16> 0.05 for the value posttest and 0.743> 0.05 for the gain so that the data homogeneous. Gain learning outcomes in the experimental class 1 .7756 (75.56%), gain learning outcomes in the experimental class 2 .5640 (56.40%). Based on the results of testing the hypothesis improving student learning outcomes obtained price sign> α ie 0.000> 0.005 with a significance level (α = 0.05) so that Ha is accepted and we can conclude that there are differences in learning outcome is taught by models Contextual Teaching and Learning and Guided models Inquiry. In addition, also obtained an increase in cognitive Siswadi experimental class that is at the level of knowledge (C1) amounted to 54.17%, of understanding (C2) of 78.85%, the application (C3) amounted to 75.62%, and for analysis (C4) amounted to 77.22% and an increase in cognitive students in the experimental class 2, namely the level of knowledge (C1) amounted to 51.67%, of understanding (C2) of 47.93%, the application (C3) amounted to 49.58%, and for analysis (C4) of 65.05%. Keywords: CTL, GI, atomic structure, learning outcomes, SPSS 21 for windows